Types and Abundance of Phytoplankton in the Genting River Estuary, Tanjung Medang Village, North Rupat District, Bengkalis Regency, Riau - Sampson Anjuando Sitorus; Eddiwan Eddiwan; Isma Mulyani (Jurnal Perikanan dan Kelautan, 2026)
The waters of North Rupat are an area with various anthropogenic activities, including tourism, industry, transportation, and activities of local communities who work as farmers, ranchers, traders, and fishermen, which may cause water pollution. The estuaries in this area have mangrove ecosystems, seagrass beds, and open waters that support the life of aquatic organisms. Phytoplankton, as primary producers, play an important role in the food chain and can serve as biological indicators of water quality and fertility. This study aims to determine the types and abundance of phytoplankton in the Genting River Estuary, Tanjung Medang Village. The study was conducted in September 2024 using a survey method to obtain primary data in the form of phytoplankton samples and water quality parameters. Samples were taken three times at weekly intervals, then identified and counted for abundance. The results showed that there were 43 types of phytoplankton consisting of Bacillariophyceae (23 types), Chlorophyceae (7 types), Cyanophyceae (8 types), Dinophyceae (1 type), Euglenophyceae (1 type), and Zygnematophyceae (3 types). The abundance of phytoplankton ranged from 6,280 to 7,560 cells/L, indicating low water fertility. Water quality parameters (temperature, salinity, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate) still support phytoplankton survival. Thus, it can be concluded that the waters of the Genting River Estuary exhibit a fairly high phytoplankton diversity but are classified as low in fertility